24.2: Invited Paper: Design of multi‐resonance thermally activated delayed fluorescence materials for organic light‐emitting diodes. (26th August 2021) - Wang, Jingxiang; Matulaitis, Tomas; Pagidi, Sudhakar; Zysman-Colman, Eli
Abstract : Two strategies to improve the performance of multiresonant thermally activated delayed fluorescence (MR‐TADF) compounds are explored. These include incorporation of units to turn on aggregation‐induced emission so as to permit use of MR‐TADF compounds at high doping concentrations, and the use of heavy atoms to increase spin‐orbit coupling to enhance reverse intersystem crossing rates. Preliminary photophysical investigations are presented.